Pengenalan Konsep Agrowisata pada Masyarakat Dataran Tinggi Gayo Kecamatan Bebesen Kabupaten Aceh Tengah - Firmansyah, Denny; Diah, Muhammad; Putra Kelana, Edi; Meilinar, Fina; Fauziani, Dinda (Aceh Journal of Community Engagement (AJCE), 2024)
The uniqueness and diversity of agricultural land culture and the cultural customs of the Takengon community have become the selling points of agrotourism in recent decades and are in great demand by the community. Takengon, in Central Aceh district, can be used as agrotourism with the presence of coffee plantation agricultural land. Agrotourism can be a solution for additional income for rural communities through the entrance to tourism, which will later attract national and international visitors. By utilizing the uniqueness of the region, the introduction of the concept of agrotourism to the Gayo Highlands Community, Bebesen District, Central Aceh Regency is needed. Both in socialization events and other promotions